"Build Rapport, Otherwise No Screening Tools in the World Are Going to Help": Frontline Service Providers' Views on Current Screening Tools for Elder Abuse. (20th December 2018) - Brijnath, Bianca; Gahan, Luke; Gaffy, Ellen; Dow, Briony
Abstract: Background and Objectives: Without an effective screening tool, accompanied by clear guidelines of what to do when elder abuse is suspected, health workers may face challenges when asking questions about elder abuse. This study aimed to find the most effective and acceptable existing elder abuse screening tool and to create guidelines for using the tool. Research Design and Methods: A rapid review of the literature identified existing validated elder abuse screening tools. Then, 5 tools (Vulnerability to Abuse Screening Scale [VASS], Elder Abuse Suspicion Index [EASI], Elder Assessment Instrument [EAI], Caregiver Abuse Screen [CASE], and Brief Abuse Screen for the Elderly [BASE]), selected based on their internal rigor, were presented to health professionals to assess the tools' relevance to their practice. Three focus groups were held with 23 health professionals in Victoria, Australia, in 2017. Data were thematically analyzed. Results: None of the tools were deemed suitable by participants for use in their practice. Criticisms of the tools included: using outdated terminology, asking binary questions, asking multiple questions at once, failure to consider the older person's cognitive status, failure to consider how culture mediates elder abuse, and failure to outline a referral pathway to those administering the tool. Participants emphasized that the screening tool must promote trust and rapport between the assessor and the older person to solicit a story on this sensitive subject. Discussion and Implications: A successful elder abuse screening tool must be concise, easy to use, account for the older person's health and social vulnerabilities, and outline a referral pathway if elder abuse is suspected.